Human ASIC1a mediates stronger acid‐induced responses as compared with mouse ASICIa. Issue 7 (15th February 2018) - Xu, Yuanyuan; Jiang, Yu‐Qing; Li, Ce; He, Mindi; Rusyniak, W. George; Annamdevula, Naga; Ochoa, Juan; Leavesley, Silas J.; Xu, Jiangping; Rich, Thomas C.; Lin, Mike T.; Zha, Xiang‐Ming
Abstract : Acid‐sensing ion channels (ASICs) are the major proton receptor in the brain and a key mediator of acidosis‐induced neuronal injuries in disease. Most of published data on ASIC function came from studies performed in mice, and relatively little is known about potential differences between human and mouse ASICs (hASIC and mASIC, respectively). This information is critical for us to better interpret the functional importance of ASICs in human disease. Here, we examined the expression of ASICs in acutely resected human cortical tissue. Compared with mouse cortex, human cortical tissue showed a similar ratio of ASIC1a:ASIC2a expression, had reduced ASIC2b level, and exhibited a higher membrane:total ratio of ASIC1a. We further investigated the mechanism for higher surface trafficking of hASICLa in heterologous cells. A single amino acid at position 285 was critical for increased N ‐glycosylation and surface expression of hASICLa. Consistent with the changes in trafficking and current, cells expressing hASIC1a or mASIC1a S285P mutant had a higher acid‐activated calcium increase and exhibited worsened acidotoxicity. These data suggest that ASICs are likely to have a larger impact on acidosis‐induced neuronal injuries in humans than mice, and this effect is, at least in part, a result of more efficient trafficking of hASICLa.—Xu, Y., Jiang, Y.‐Q., Li, C., He, M., Rusyniak, W. G., Annamdevula, N., Ochoa, J., Leavesley, S. J., Xu, J., Rich, T. C., Lin, M. T., Zha, X.‐M. Human ASICIa mediates stronger acid‐induced responses as compared with mouse ASICIa. FASEB J. 32, 3832–3843 (2018). www.fasebj.org